ELABORASI PROGRAM ANTI PERUNDUNGAN DALAM SEKOLAH RAMAH ANAK PADA KURIKULUM PENDIDIKAN PANCASILA - Damayanti, Siska; Adnin, Ismi; Rachma Ramadhan, Abhi; Al Ghifari, M. Alif; Fatihah, Husnul (Jurnal Sosial Humaniora, 2025)
The issue of bullying, especially within the school context, has garnered widespread attention, primarily due to the serious consequences that can impact the psychosocial development of children and adolescents. Efforts and appropriate strategies are needed to address this issue effectively. The aim of this research is to delve deeply into the development and implementation process of a Bullying Prevention Program within a child-friendly school integrated into the Civic Education curriculum, thus providing innovation in addressing bullying within the Civic Education curriculum. This research adopts a qualitative research approach using a case study method. Data collection processes involve interviews, observations, and documentation. The research findings indicate that the Bullying Prevention Program within the Civic Education curriculum is supported by active involvement from Civic Education teachers, school staff, and adequate school environment facilities. The implementation of the Bullying Prevention Program within a child-friendly school integrated into the Civic Education curriculum involves efforts and innovative teaching strategies by Civic Education teachers to foster positive bullying prevention behaviors.